Clinician perceptions on barriers and facilitators to 1‐year surveillance colonoscopy completion in survivors of colorectal cancer - C. Natasha Kwendakwema; Talor Hopkins; Ari Bell‐Brown; Vlad V. Simianu; Veena Shankaran; Rachel B. Issaka (Cancer Medicine)
Abstract Introduction Colorectal cancer (CRC) is the second leading cause of cancer deaths in the United States. Surveillance colonoscopy is recommended 1‐year after surgical resection for patients with stage I‐III CRC; however, only 18%–61% of CRC survivors complete this test. This study describes clinician‐identified barriers and facilitators to surveillance colonoscopy among CRC survivors. Methods We conducted semi‐structured interviews with clinicians until thematic saturation was achieved. Interviews were analyzed using the social cognitive theory. Results Thirteen clinicians were interviewed, and all identified health system‐level barriers to surveillance colonoscopy completion; the most common being fragmented care due to patients receiving care across many health systems. Clinicians also identified social determinants of health barriers (e.g., geographical distance between patients and health systems) to 1‐year surveillance colonoscopy completion. Conclusions Clinicians identified several potentially modifiable barriers to 1‐year surveillance colonoscopy completion which, if addressed, could improve post‐treatment care and outcomes among stage I‐III CRC survivors.